2022
DOI: 10.18632/aging.204251
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lipolysis promotes physiological fitness in Drosophila melanogaster

Abstract: Since interventions such as caloric restriction or fasting robustly promote lipid catabolism and improve aging-related phenotypical markers, we investigated the direct effect of increased lipid catabolism via overexpression of bmm ( brummer , FBgn0036449), the major triglyceride hydrolase in Drosophila, on lifespan and physiological fitness. Comprehensive characterization was carried out using RNA-seq, lipidomics and metabolomics analysis. Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…In Drosophila , lacking both maternal and zygotic Bmm activity causes embryonic lethality and embryos produced by Bmm-deficient female flies with WT males hatched nearly 40% [ 15 ]. Overexpression of Bmm robustly increased fecundity in female flies [ 33 ] and accumulation of lipids in ovary is essential for oogenesis [ 7 ]. Our results showed that loss-of-BmBmm activity caused reduced egg production and complete infertility in female silkworms due to TG deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila , lacking both maternal and zygotic Bmm activity causes embryonic lethality and embryos produced by Bmm-deficient female flies with WT males hatched nearly 40% [ 15 ]. Overexpression of Bmm robustly increased fecundity in female flies [ 33 ] and accumulation of lipids in ovary is essential for oogenesis [ 7 ]. Our results showed that loss-of-BmBmm activity caused reduced egg production and complete infertility in female silkworms due to TG deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Further overexpression of ATGL-1 (homolog of ATGL) extends the lifespan in C. elegans while the reduction of ATGL-1 function suppresses the longevity of the long-lived mutants eat-2 and daf-2 57,58 . Similarly, overexpression of brummer (bmm, the major TG hydrolase in Drosophila) improved several healthspan outcomes like fertility, locomotion, mitochondrial function, and oxidative metabolism in Drosophila 59 . Our present studies support these previous findings in lower organisms and show that lipolytic stimulation using β3-AR agonists promotes metabolic health in aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when bmm is suppressed across all tissues or metabolic speci c tissues through RNA interference, it results in a short lifespan of Drosophila (Nazario-Yepiz et al 2021). On the other hand, overexpression of bmm leads to a reduction in the size of lipid droplets, whereas a de ciency in bmm increases triacylglycerol (TAG) storage, leading to obesity and a reduction in lifespan (Shang et al 2022). At rst sight it is challenging to judge how the activity of bmm could in uence lifespan, but there exists a possible scheme for its action.…”
Section: Discussionmentioning
confidence: 99%